Penerapan Media Pembelajaran Wordwall dalam Menunjang Pemahaman Siswa MA Darul Lughah Wal Karomah pada Pembelajaran Bahasa Indonesia - Ummi Maulidatus Syahro; Mohammad Saied; Hemas Haryas Harja Susetya (Jurnal Bintang Pendidikan Indonesia, 2025)
This study was motivated by the low motivation and boredom of students in learning Indonesian, which is still dominated by conventional methods and results in less optimal conceptual understanding. The purpose of this research is to implement Wordwall as an interactive learning medium to improve students’ conceptual comprehension, interest, and motivation. This research employed a qualitative method with a descriptive qualitative approach. The subjects were X students of MA Darul Lughah Wal Karomah Kraksaan. Data were collected through observation, interviews, and documentation. The findings revealed that Wordwall successfully created a more engaging and enjoyable learning atmosphere compared to traditional teaching methods. Its interactive features, such as quizzes, word-matching activities, and word-search exercises, stimulated students’ enthusiasm and encouraged them to actively engage with the material. The scoring system and timer also fostered a healthy sense of competition, which further motivated students to participate. However, some limitations were identified, including the possibility of cheating, the relatively small font size, and the time-consuming process of preparing questions. Despite these challenges, the implication of this study suggests that Wordwall can serve as an innovative alternative medium for teaching Indonesian, providing both meaningful learning experiences and enhanced learning quality.